2015
DOI: 10.1007/s13218-015-0349-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensemaking in Intelligent Health Data Analytics

Abstract: A systemic model for making sense of health data is presented, in which networked foresight complements intelligent data analytics. Data here serves the goal of a future systems medicine approach by explaining the past and the current, while foresight can serve by explaining the future. Anecdotal evidence from a case study is presented, in which the complex decisions faced by the traditional stakeholder of results-the policymakerare replaced by the often mundane problems faced by an individual trying to make s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Lastly, users also actively combine different systems and appropriate them for their own settings [9]. Rooksby and colleagues [39], studied how people use various tracking devices as part of their everyday life, and concluded that we cannot expect "people to act as rational data scientists".…”
Section: Sensemakingmentioning
confidence: 99%
“…Lastly, users also actively combine different systems and appropriate them for their own settings [9]. Rooksby and colleagues [39], studied how people use various tracking devices as part of their everyday life, and concluded that we cannot expect "people to act as rational data scientists".…”
Section: Sensemakingmentioning
confidence: 99%
“…This is visible by the predominance of the categories diagnosis and self-tracking, a total of 43.8% of the papers. These types of systems have been proposed as having the potential to change how health care is to be provided, not only by providing immediate support to a sufferer, through improving adherence to a treatment or predicting episodes, as we have seen in the reviewed papers, but also by aggregating different health data streams across patients (big data) and helping see populationwide trends, providing the possibility of advancing theoretical frameworks for mental health and providing evidence for effectiveness of different therapies by making use of the multivariate nature of available data from different sufferers [24,32,158]. However, we would also like to point out interesting and under-represented research directions in the analyzed corpus.…”
Section: Implications and Future Directions For Research And Practicementioning
confidence: 99%
“…Users also need to set goals-or create "images" of where they are heading and how to integrate these processes with their everyday life-that could be done through sharing practices and ideas in on-line forums. The study by Boman and Sanches [6] shows how Fitbit users make sense of their tracked step data by sharing practices in the online forums, not only by helping each other making sense of data, but also by finding alternative practices using the step counter (e.g., in a bicycle), or together developing solutions for when the device is found to be incorrectly making calculations. Similar to how many know that they are supposed to walk 10,000 steps per day and that step counters can help keep track, normative statements about stress or performance around skin conductance data might have to be communicated.…”
Section: Proto-practices Around Skin Conductancementioning
confidence: 99%